1993
DOI: 10.1300/j070v01n03_06
|View full text |Cite
|
Sign up to set email alerts
|

Attributions of Blame in Child Sexual Abuse Victims

Abstract: Attributions of self-blame, molester-blame, and blame for consequences to the victim's family were assessed in male and female child sexual abuse victims across three age groups: children (8-12); adolescents (13-17); and adults who were molested as chil-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 10 publications
6
40
0
Order By: Relevance
“…This study examined how age at abuse discovery was related to abuse-specific attributions at discovery and over time. The limited research on abuse-specific attributions is contradictory with one study showing children having more (Hazzard, Celano, Gould, Lawry, & Webb, 1995) and another less (Hunter et al, 1992) self-blame than adolescents or adults. The theoretical literature suggests competing hypotheses for which age group is likely to make more self-blame attributions for the abuse.…”
Section: Age and Abuse-specific Attributionsmentioning
confidence: 90%
See 4 more Smart Citations
“…This study examined how age at abuse discovery was related to abuse-specific attributions at discovery and over time. The limited research on abuse-specific attributions is contradictory with one study showing children having more (Hazzard, Celano, Gould, Lawry, & Webb, 1995) and another less (Hunter et al, 1992) self-blame than adolescents or adults. The theoretical literature suggests competing hypotheses for which age group is likely to make more self-blame attributions for the abuse.…”
Section: Age and Abuse-specific Attributionsmentioning
confidence: 90%
“…Most studies of general attributional style in children and adolescents find no gender differences (Gotlib, Lewinsohn, Seeley, Rohde, & Redner, 1993;Quiggle, Garber, Panak, & Dodge, 1992;Mezulis, Hyde, & Abramson, 2006), although one study reported adolescent women were more likely to make internal attributions for negative events (Gladstone, Kaslow, Seeley, & Lewinsohn, 1997). Similarly, studies on abuse-specific attributions find no gender differences in levels of self-and perpetrator-blame (Hunter et al, 1992;McGee et al, 2001). Despite this paucity of empirical support, gender differences in abuse-specific attributions were explored because so few studies have done so, none has considered changes in abuse-specific attributions as a function of gender, and conceptually self-blame attributions have been viewed as particularly important for women's adaptation to CSA (Cutler & Nolen-Hoeksema, 1991).…”
Section: Gender and Abuse-specific Attributionsmentioning
confidence: 98%
See 3 more Smart Citations